2007
DOI: 10.1038/sj.ejcn.1602604
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of feeding practices in five European countries: an exploratory study

Abstract: Objective: To gain an insight into parental perceptions of infant feeding practices in five European countries. Design: An exploratory investigation using focus group discussions. Various aspects addressed included social and cultural setting for the consumption of food, infant feeding practice and behaviour, consumer health awareness and sources of information, and attitudes towards a healthy infant diet. Setting: Focus group participants were recruited from centres in five countries, Germany, Italy, Scotland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
109
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(130 citation statements)
references
References 26 publications
(38 reference statements)
16
109
3
2
Order By: Relevance
“…This contrast in when to commence complementary feeding has previously been reported to vary by country [28][29][30]. A recent online questionnaire study of 3607 mothers, suggested that those who weaned early were more focused on putative signs of readiness, whereas those weaning later were more focused on the infant reaching the recommended age.…”
Section: Discussionmentioning
confidence: 88%
“…This contrast in when to commence complementary feeding has previously been reported to vary by country [28][29][30]. A recent online questionnaire study of 3607 mothers, suggested that those who weaned early were more focused on putative signs of readiness, whereas those weaning later were more focused on the infant reaching the recommended age.…”
Section: Discussionmentioning
confidence: 88%
“…127,131,139,222,224,227,228 As captured in Heinig et al's study 131 mothers had no preconceived plans around when to introduce solids ("I didn't really know exactly when [to introduce solids] or I really didn't know. I thought I'd just go off it when she gave me the cue.…”
Section: Sub-theme: Behavioural Cuesmentioning
confidence: 99%
“…177,220 Convenience and time pressure also influenced food choices, with quick meal choices that satisfied hunger winning out over healthier options. 228,233 While cost was found to influence food choices especially in low income families, 177,230,[233][234][235] food was also seen as a relatively inexpensive commodity that had immediate satiety effects.…”
Section: Sub-theme: Coping Strategiesmentioning
confidence: 99%
See 2 more Smart Citations